FIELD DEVELOPMENT STUDY OF ULUMBU GEOTHERMAL FIELD BASED ON RESERVOIR SIMULATION - KURNIAWAN , IQBAL
Ulumbu Geothermal Field is located in Wewo, Manggarai District, East Nusa Tenggara, Indonesia. This field is owned by PT. PLN (Persero) and has a total installed capacity of 10 MWe. The geothermal system of this field is a steam cap underlying a liquid-dominated reservoir with a temperature of 230-240oC. Integrated reservoir study by using reservoir simulation is mandatory as PT. PLN (Persero) is planning to increase the capacity by adding two more additional units having capacity 2ÃƒÂ—20 MWe in 2020 and 2024. The integrated reservoir study by using reservoir simulation is needed to calculate the potential generation, to increase the reservoir characteristics understanding, and to do reservoir performance forecasting by using various field development scenarios. The modeling process was carried out by using TOUGH2 V.2.0 with EOS 1. The modeled area is approximately 100 km2 with a vertical extension of 4.4 km. The numerical model of Ulumbu Geothermal Field was successfully built by carrying two steps of calibration. The first calibration was an initial state validation by using temperature profiles of 3 drilled wells, heat-mass flow from the conceptual model, and 4 surface manifestations mass rate. The second calibration was a history matching by using the actual production test data and well performance history. Reserve calculation was carried out by using two methods, full factorial experimental design method and heat stored method. The Monte Carlo simulation for both methods shows a potential generation of 95 MWe. The reservoir performance forecasting indicates that a total generation of 50 MWe with makeup wells from two phase zone as the best scenario. The scenario needs 13 development wells with 5 make-up wells and 2 injection wells. The temperature and pressure decrease at a rate of 5 bar and 10oC in 30 years.